2021
DOI: 10.21203/rs.3.rs-1123463/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccination uptake strongly predicts averted deaths of older people across Europe

Abstract: Background: Nationwide COVID-19 (coronavirus disease 2019) vaccination campaigns have been effective to avert as many as 51% deaths in people aged ≥60 years in the European region between December 2020 and November 2021, though broad heterogeneity has been observed in the percentage of averted deaths across the different European countries. Methods: We downloaded data of vaccine uptake and efficacy into an Excel Worksheet, and we then performed univariate (Spearman’s correlation) and multivariate (multiple lin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Other parameters, such as medical [ 7 ], genetic [ 8 ], environmental [ 9 ], physical [ 10 , 11 ], mental/psychological [ 12 ], social [ 13 ], economical [ 14 ], and political [ 15 ], whose effect cannot be precisely determined, at least at an individual level, are believed to contribute to country-specific CFR disparities. Last, concerning vaccination for SARS-CoV-2, it has been reported that vaccination uptake is closely associated with elderly people saved, independently of the vaccine type administered [ 16 ]. Emerging data further support the efficacy and effectiveness of COVID-19 vaccines in terms of public health consequences [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other parameters, such as medical [ 7 ], genetic [ 8 ], environmental [ 9 ], physical [ 10 , 11 ], mental/psychological [ 12 ], social [ 13 ], economical [ 14 ], and political [ 15 ], whose effect cannot be precisely determined, at least at an individual level, are believed to contribute to country-specific CFR disparities. Last, concerning vaccination for SARS-CoV-2, it has been reported that vaccination uptake is closely associated with elderly people saved, independently of the vaccine type administered [ 16 ]. Emerging data further support the efficacy and effectiveness of COVID-19 vaccines in terms of public health consequences [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mattiuzzi et al ( 36 ) measure the association between the percentage of averted deaths of older people and the percentage of vaccine uptake in each corresponding European country. The authors used data on vaccine uptake and efficacy to perform univariate (Spearman’s correlation) and multivariate (multiple linear regression analysis) correlations to determine the association of the percentage of averted deaths with vaccine uptake and the type of vaccine administered.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the National Ministry of Health and the Centers for Diseases Control are the main sources of these data. Nonetheless, depending on the approaches applied, other sources (secondary data) are also considered, as in Mattiuzzi et al ( 36 ), which used the data produced by Meslé et al ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation